Melatonin supplementation counteracts fiber loss in knee ligaments of diabetes-induced rats - Olga Adamska; Artur Wnuk; Agnieszka Kamińska; Małgorzata Poniatowska; Bartosz Maciąg; Maciej Kamiński; Artur Stolarczyk; Maima Matin; Atanas G. Atanasov; Atanas G. Atanasov; Atanas G. Atanasov; Marcin Łapiński; et al. (Frontiers in Pharmacology, 2024)
Diabetes mellitus (DM) is a prevalent metabolic disease. The clinical impact of sustained hyperglycemia on ligament healing has not been well characterized. Diabetes is a known cause of macro-, microvascular, and diabetic ulcer healing difficulties among tissues. Therefore, we aimed to investigate the healing potential occurring in injured and healthy ligaments among diabetic and healthy individuals using a rat model. We hypothesize that DM may contribute to altering the knee medial collateral ligament (MCL), thus its morphology, biochemical fitness, and functionality. The study cohort consisted of 40 rats. The animals were randomized into four equal groups. Groups I and II (20 rats) received saline subcutaneously and served as controls. Groups III and IV (20 rats) were injected with a single dose of streptozotocin (STZ). All animals underwent surgery to cut the left tibial collateral ligament in the hind limb and suture it. The access site was sutured to create inflammation and study the regenerative capacities of animals with normal carbohydrate metabolism and pharmacologically induced diabetes. Each animal then underwent sham surgery to access and suture the right tibial collateral ligament in the hind limb without ligament intervention. After the animals had undergone surgeries, groups II and IV were given melatonin supplementation for 4 weeks. Rats with DM presented with more fibrosis and calcification of the MCL and decreased healing potential. Treatment with melatonin in diabetic rats mitigated alterations and improved the antioxidant status of ligaments from the diabetic group.